Kemampuan Berpikir Kritis Matematis Siswa: Studi dengan Model Probing-Prompting dan Konvensional - Ninda Kristin; Candra Ditasona; Jitu Halomoan Lumbantoruan (Brillo Journal, 2021)
This study aims to determine how students critical thinking ability who study with probing-prompting and conventional learning models are. This research is a quantitatif research with a quasi-experimental design group. The research population was all students of class X SMK Setih Setio 2 Muara Bungo, Jambi. The research sample consisted of two classes with a sample size of 62 people determined by simple random sampling, namely X MM as the control class using the conventional learning model and X AK as the experimental class using the Probing-Prompting learning model. Requirements analysis test has been carried out so that the data obtained are not normally distributed and not homogeneous. The hypotheses were analyzed using the U-Mann Whitney test at a significant level of α=0,05. Based on data analysis and hypothesis testing, it was found that: (1) there were differences in students' critical thinking skills taught using probing-prompting and conventional learning models, and (2) there is an increase in students' critical thinking skills taught by using probing-prompting and conventional models.